Piezoelectric energy floor tiles performance and effectiveness as building energy conservation measures for different types of buildings in Malaysia - Puteri Aisyah, Megat Shariffudin (2022)
In the era of urbanization, energy or mainly electrical energy is one of the main drivers of the economic, social, and environmental sustainability development. Buildings have been considered as one of the biggest contributors in the greenhouse gas (GHG) effect and other negative impacts on the environmental worldwide. Due to the high number of the CO2 emission recorded, many initiatives or strategies have been introduced to address the issues and further helping to reduce carbon emissions mainly through the buildings decarbonizations as well as finding new reliable and cleaner ways of energy production essentially. Such initiatives include the implementation of sustainable and renewable energy technologies as building energy conservation measures to achieve low emission and optimize energy consumption in a building. Many of the technologies present today are based on the concept of energy harvesting along with the electromechanical, electromagnetism and piezoelectric mechanism integrated into the system. This study concentrates on the hybrid properties of energy harvesting which involved the mechanism of electromechanical and piezoelectric in one energy harvesting system. Several piezoelectric energy harvesting floor tiles technology have promising potential in helping the development of low energy building. Specifically in Malaysia, this kind of mechanism could outperform the solar energy harvesting system since the piezoelectric energy harvesting technology could help both in the sense that it takes less place compared to solar energy harvesting system and the main source for this particular technology is in the form of human movement which certainly will never deplete in time. From the study, it was noted that as long as the cash flow for such technology can be manage properly, the system mechanism could help in the reduction of more than 90% of total building energy consumption and also carbon emission with payback period of less than a year from its baseline year.